Cover image, Volume 31 Issue 10. (17th September 2018) - Schregel, Katharina; Nazari, Navid; Nowicki, Michal O.; Palotai, Miklos; Lawler, Sean E.; Sinkus, Ralph; Barbone, Paul E.; Patz, Samuel
Abstract : The cover image, by Katharina Schregel et al., is based on the Special Issue Research Article Characterization of glioblastoma in an orthotopic mouse model with magnetic resonance elastography, https://doi.org/10.1002/nbm.3840 . This project has received funding from the European Union's Horizon 2020 research and innovation programme under grant agreement No 668039.